Investigation of relationship of the mitochondrial DNA 16189 T > C polymorphism with metabolic syndrome and its associated clinical parameters in Turkish patients - (:unkn) unknown (HELLENIC ENDOCRINE SOC, 2011)
OBJECTIVE: Mitochondrial DNA (mtDNA) polymorphisms have been implicated in the pathophysiology of human diseases. Among them, a T>C nucleotide transition on the 16189 nucleotide position of mtDNA has been studied in several metabolic diseases including diabetes and obesity. In this study we aimed to investigate the association of this polymorphism among Turkish metabolic syndrome patients. DESIGN: A total of 220 cases (70 MetS patients and 150 healthy control subjects) were evaluated for their mtDNA 16189 variant by PCR-RFLP technique. In addition, clinical and biochemical variables, such as cholesterol levels, body fat percentage, insulin resistance and presence of type II diabetes, were also evaluated. RESULTS: Overall frequency of polymorphic C allele was determined as 0.19 without a significant association with type II diabetes and metabolic syndrome. This may be partly due to ethnical differences of populations studied and may also be related to other genetic and environmental factors. Moreover, there were no significant associations with biochemical variables among metabolic syndrome patients, except LDL and suppressed cortisol (sup-cortisol) levels. Low levels of LDL and sup-cortisol were significantly associated with the mtDNA 16189 variant, though the biochemical mechanism underlying this effect is not clear. CONCLUSIONS: This is the first study involving a Turkish population on the mtDNA 16189 T>C polymorphism. Further studies with larger cohorts will be needed to elucidate its relation with metabolic syndrome as well as lipid metabolism.
Keywords: Diabetes; Metabolic syndrome; Mitochondrial DNA; TYPE-2 DIABETES-MELLITUS; BODY-MASS INDEX; INSULIN-RESISTANCE; VARIANT; DISEASE; GLUCOSE; GENOME; PHENOTYPES; SEQUENCE; GROWTH